Utilização de geotecnologia para avaliação da piscicultura na sub-bacia hidrográfica do Arroio Guaçu, na bacia hidrográfica do Paraná 3, região oeste do Paraná - Werneck, Pedro Rondon (2023)
The objective of this work was to use geotechnology in the evaluation of aquaculture production areas and their input of effluents in the Arroio Guaçu sub-basin. In the methodology, Digital Elevation Models (MDE) were used for the delimitation of the sub-basin area, obtained from INPE data, and the municipal vectors were obtained from the IBGE website. Algorithms from the QGIS program were used, such as r.fill.dir, OpenStreetMap, r.watershed and r.water.outlet. Several morphometric calculations of the sub-basin area were performed. The fish ponds were divided into four classes, I between 300 to 3,000 m², II between 3,001 and 6,000 m², III between 6,001 and 10,000 m² and IV greater than 10,001 m². Calculations of land use,occupation, altimetry, slope and ordering of river courses were also made, in addition to estimates of nitrogen and phosphorus contribution calculations. The morphometric results indicate an area of 1,186.02 km², the sub-basin is exceptionally well drained, with a low risk of occurrence of major floods, its channels are sinuous. The classes of ponds show that there are 750.70 ha of water depth, totaling 2542 ponds, most of which were class I with 237.20 ha of water depth with 1.723. Estimates of total nitrogen and total phosphorus inputs during rearing were respectively 1,524,966.02 kg and 186,160.00 kg and during harvesting were respectively 60,917.81 kg and 12,344.63 kg. It is concluded that the data obtained in this work can help both public and private managers, for the better organization and management of water and soil resources in the Arroio Guaçu sub-basin area.